Use of Village Funds in the Accelerated Convergence Program for Stunting Prevention - Hendriyanto , Nur; Prakoso, Lukman Yudho (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
This research aims to provide an overview (description) and analyze several Village Fund programs related to stunting prevention and the extent of the success rate of the impact of using Village Funds on reducing rates of malnutrition and stunting in Ketitanglor Village. Research technique in the form of a literature review study of several appropriate articles, Regulations of the Ministry of Villages, Development of Disadvantaged Regions and Transmigration, APBD desa Ketitanglor, Bojong District, Pekalongan Regency and qualitative analysis. Based on the research results of several articles, it shows that stunting convergence must receive serious attention from the lower level of government, namely the village. The Central Government must provide clear regulations and a legal umbrella regarding the use of Village Funds for accelerated convergence in stunting prevention in villages. It can be concluded that stunting convergence must be carried out in an organized, coordinated manner and involve all elements, including health workers, village stakeholders including community leaders, social religious institutions, non-governmental organizations and also village government, supra-village government at the sub-district, district/city level and Provinces and Central Government.